Development of the Android-based “PEPOKI” application to enhance learning motivation among fifth-grade students - Febrianty, Hana; Nugraha, Rana Gustian; Saputra, Yudha Munajat (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
The limited use of technology-based learning media often results in monotonous classroom activities, which can negatively affect students’ learning motivation. This study aims to develop an Android-based learning application called PEPOKI, assess its feasibility, and examine its effectiveness in improving students’ motivation in Social Studies, particularly on the topic of Indonesia’s Proclamation of Independence. Employing a Research and Development (R&D) design using the ADDIE model, data were collected through expert validation instruments and student questionnaires. The developed application was evaluated by material experts and media experts, yielding feasibility scores of 82.5% and 91%, respectively—both categorized as “highly feasible.” The effectiveness test involving experimental and control groups showed that the use of PEPOKI significantly increased students’ motivation, as reflected in the N-gain score of 0.35 (moderate category) in the experimental class, compared to 0.22 (low category) in the control class. These findings indicate that the PEPOKI application is both feasible and effective as a learning medium and can serve as an innovative tool to foster greater motivation among fifth-grade students in primary schools.